COMPARISON OF THE NUMBER OF ERYTHROCYTES IN 3 ML, 2 ML, & 1 ML OF BLOOD SAMPLES WITH K2EDTA ANTICOAGULANTS AFTER A 4-HOUR DELAY IN THE DR. H. ABDUL MOELOEK BANDAR LAMPUNG HOSPITAL - Syuhada; Priyayi, Hemas; Putri , Bella Tania; Nabigha, Zehan Aura; Triwahyuni, Tusy (Transpublika Publisher, 2022)
Background: The volume of blood samples, especially the number of erythrocytes in laboratory examinations, has an important role in determining the results of the diagnosis, in this case pre-analytic errors often occur so that a definite diagnosis will be difficult to establish. Therefore, research on the comparison between the results of the examination of the number of erythrocytes in the volume of blood samples of 3 mL, 2 mL, and 1 mL after being delayed for 4 hours with K2EDTA anticoagulant helps to determine a definite diagnosis from laboratory tests, one of which is the count of the number of erythrocytes. Research purpose: it aims to identify the comparison of erythrocytes in the volume of blood sample 3 ml, 2 ml, and 1 ml with k2edta anticoagulant after postponed for four hours. Research methods: the study uses primary data with hematology analyzer in rsud Dr.abdul moeloek bandar lampung. This type of research is a quantitative, using observational analtic design with a cross sectional view and with consecutive method, through hematology analysis using a alayzer mindray bc-3600 hematology. The research has 50 respondents. Results: the results of erythrocytes comparison between blood volume 3 ml, 2 ml and 1 ml (ml) with k2edta anticoagulant after 4 hours have different results but statistically the results have the same with 3 ml, that show the lowest result. Conclusion: there is no significant differences between the examunation of the erythrocytes with the volume of blood sample 3 mL, 2 mL, and 1 mL in the vacutainer k2edta tube after postponed for four hours.